Active Cycle of Breathing Decrease Dyspneu on Tuberculosis Patient - Tintin Sukartini; Sriyono Sriyono; Iwan Widia Sasmita (Universitas Airlangga, 2008)
Introduction: Active cycle of breathing as one of the nursing intervention can solve respiratory problems (such as caused by tuberculosis). Tuberculosis can cause fibrosis tissue in lung. Fibrosis makes elasticity and compliance of lung decrease result in air ventilation and oxygenation disorder, so it will increase Respiratory Rate (RR) and dyspnea. The objective of this study was to analyze the effect of active cycle of breathing technique on reducing RR and dyspnea. Methods: A quasy experimental purposive sampling design was used in this study. There were 14 respondents who met to the inclusion criteria, divided into 7 respondents for intervention group and 7 respondents for control group. Data were analyzed by using Paired t-Test, Independent t-Test, Wilcoxon Signed Rank Test and Mann Whitney U-Test with significance levelα≤0.05.Results: The result showed that active cycle of breathing had significance level on decreased RR (p=0.002) and dyspnea (p=0.014).Conclusion: It can be concluded that active cycle of breathing has effect decrease RR and dyspnea. It recommended to use active cycle of breathing continuously to decrease dyspnea and to enhance quality of life on Tuberculosis patient.